Examining Scientific Evidence in US and Chinese Courts: A Comparative Study - Bangda Chen (Journal of Forensic Science and Medicine, 2016)
The critical examination of scientific evidence is crucial in attempting to distinguish genuine science from "junk science" and provides judges with an important basis upon which to determine the credibility of expert witnesses giving scientific evidence. From studying the law in the USA, we learn that the process for examining scientific evidence in court is based upon full discovery of the proposed evidence before trial and the availability of expert witnesses at trial to testify orally and be examined and cross-examined. Empirical studies suggest that the opportunities to critically examine scientific evidence in Chinese courts are not so freely available. Discovery is neglected, thus limiting the effectiveness of cross-examination, and current rules do not encourage oral testimony or effective cross-examination. To solve these problems, the disclosure duty should be put on the prosecution, rather than on the defendant. Scientific evidence should be discovered. Disclosure must include the basis, process, material relied upon, and methods of forensic appraisals. In the trial process, the prosecution has transferred the case file to court, where the defendant will be able to copy the scientific evidence. The neutrality of expert assistants established by article 192 of the new Criminal Procedural Law should be strengthened.